A survey on orchids in selected trails of Gunung Nuang forest reserve - Khor, Hong Eng; Go, Rusea; Khor, Pei Wen; Abdullah, Janna Ong (Universiti Putra Malaysia Press, 2010)
Gunung Nuang, which is the highest mountain peak in Selangor at 1493 m, marks the meeting point of three Malaysian states, namely Negeri Sembilan, Pahang, and Selangor. Gunung Nuang Forest Reserve comprises of lowland dipterocarp, hill dipterocarp, upper hill dipterocarp, and montane dipterocarp forest, covering 3.9% of Selangor land area. Starting from 2005, several collection trips were made to observe and document the flora from the family of Orchidaceae. As a result, 27 species of orchids were found on the selected trails, while 11 taxa remain unidentified. From the collected specimens, 34.9% of Selangor's orchids were represented by the results, indicating the rather high species diversity in the area. From the collections, five species are new records to Selangor. All the specimens were identified based on their morphological vegetative features and floral structures.